Preferred Learning styles among Junior High School students Using non Cognitive Diagnostic Assessment - Tia Rahmatika; Azmar; Ifan Munif Fajriawan (EDULANGUE, 2023)
Every student possesses individual learning styles, making it crucial to examine their preferred approaches as a means of designing courses and implementing effective instructional methods. The aim of this research endeavor was to identify the predominant learning style among junior high school students, along with discerning any gender-related associations with specific learning styles. Employing a descriptive quantitative research methodology, data were collected from 97 participants via non-cognitive diagnostic assessments. The results revealed that the visual learning style emerged as the most favored choice, with a prevalence rate of 60.8%. It was followed by the auditory style (12.4%), kinesthetic style (9.3%), visual-auditory style (7.2%), visual-kinesthetic style (7.2%), and auditory-kinesthetic style (3.1%). In terms of gender distribution, a significant majority of male students exhibited a preference for the visual style (42.3%), while the visual style also predominated among female students (18.6%). These findings hold valuable implications for fostering pedagogical excellence. Based on these results, educators are strongly advised to embrace diverse teaching methods and design multifaceted activities that encompass and accommodate the different learning styles exhibited among students.